The Abductive Hypothesis as a Teaching Strategy for Research in the Classroom - Moreno Torres, Mónica; Carvajal Córdoba, Edwin; Arango Escobar, Yeimy (Íkala, Revista de Lenguaje y Cultura, 2012)
This text addresses the question of how to translate abductive hypothesis in a teaching strategy for classroom research. Its understanding and interpretation is based on methodological procedures of the Peircean speech applied in education and literature, and of the logic of scientific reasoning based on abduction, deduction and induction. A teaching case is presented in which procedures of the abductive hypothesis are applied, which indicates as a result, the advantages of education for the promotion of rational freedom in the classroom, respecting the individual differences of students, their physical welfare and aesthetic taste. Finally, it was concluded that the application of abductive hypothesis in education requires creative use of knowledge, founded on the logic of scientific reasoning, which breaks with the rationalist view of induction and deduction, and in conception of methods of science as liberating acts to stimulate the ability to investigate, judge and act in the midst of diversity, in opposition to a homogeneous view of society.